# Geometry

posted by Lauren

Which is logically equivalent to ~p -> q?
a.) ~q -> p
b.) ~q -> ~p
c.) q -> p
d.) q -> ~p

1. bobpursley

I am not certain of your usage of ->, but I have a technique you can use that will work always.

Construct a truth table, such as this:
http://www.gateways2learning.com/SetTheory/EquivalentStatements.pdf

2. Steve

It is just like your previous post. The contrapositive of

~p -> q

reverses the direction of implication, and the logical values:

~(q) -> ~(~p)
~q -> p

## Similar Questions

1. ### math

Which statement is logically equivalent to ~a ¨ b?
2. ### discrete mathematics with applications

Determine which of the following pairs of statements forms are logically equivalent. Justify your answer using truth tables and include a few words of explanation. Read "t" to be a tautology and "c" to be a contradiction: 26. (p^q)v(p^r)and(pvq)^r …
3. ### Discrete math

Question: Use logical equivalnces to show that the propositions !p -> (q->r) and q -> (p v r) are logically equivalent. I AM SO DAMN CONFUSED! I tried to solve !p -> (q -> r) first and I only got to !p -> (!q v r) …
4. ### math

Question: Use logical equivalnces to show that the propositions !p -> (q->r) and q -> (p v r) are logically equivalent. I AM SO DAMN CONFUSED! I tried to solve !p -> (q -> r) first and I only got to !p -> (!q v r) …
5. ### Geometry

In logic, which of the following is said to be logically equivalent to the original statement?
6. ### Geometry

A conditional statement is always logically equivalent to its a.) contrapositive b.) converse c.) conjunction d.) inverse
7. ### Geometry

Look at the statement below. “All dogs are mammals.” Which of these is a logically equivalent statement?
8. ### Geometry

If Gina cleans her room, then she will go to the mall. Which of these is logically equivalent to the given statement?
9. ### math

If Tom buys a red skateboard, then Anne buys pink in-line skates." Which statement below is logically equivalent?
10. ### Logic / Discrete Mathematics

Show that "¬p Λ q is logically equivalent to p → ¬q" . I'm not sure if the conditional identity is correct, but what I did was I negated the whole second condition and it immediately became equal to the first?

More Similar Questions